Faunistic Composition, Ecological distribution and rarity assessement of swallowtail butterflies (Lepidoptera: Papilionidae) in Sarawak - Cheok, Yin Hui (Universiti Malaysia Sarawak (UNIMAS), 2017)
Butterflies in the family Papilionidae are important biological indicators to the alteration of surrounding environment. Hence, fundamental knowledge which could be gathered from baseline data from historical collections, as well as active sampling, is important. Both active sampling and voucher specimens examination were used to retrieve information of Papilionidae species occur in Sarawak. Results from this study revealed there are 34 species of Papilionidae occur in Sarawak and their ecological distribution of most species were restricted to the Mixed Dipterocarp Forest. The most common generalist species were Arisbe evemon orthia, Menelaides memnon memnon, Graphium sarpedon sarpedon, Trogonoptera brookiana brookiana and Graphium agamemnon agamemnon. Many species were found to be rare species with low abundance, restricted geographical distribution and narrow biotope exploitation. Mixed Dipterocarp Forest supports the highest number of the Papilionidae species and individuals in Sarawak, probably due to the favorable habitats and high abundance of larval host plants and food sources. However, other forest types are also very important as they may support endemic species. Constant sampling with higher sampling effort focusing on untouched pristine forest and highlands are required to reveal the distribution of Papilionidae species in Sarawak. Ecological distribution and rarity status of Papilionidae species are hoped to contribute to the conservational management of the Swallowtails.